2021
DOI: 10.3390/antibiotics10121443
|View full text |Cite
|
Sign up to set email alerts
|

New Auranofin Analogs with Antibacterial Properties against Burkholderia Clinical Isolates

Abstract: Bacteria of the genus Burkholderia include pathogenic Burkholderia mallei, Burkholderia pseudomallei and the Burkholderia cepacia complex (Bcc). These Gram-negative pathogens have intrinsic drug resistance, which makes treatment of infections difficult. Bcc affects individuals with cystic fibrosis (CF) and the species B. cenocepacia is associated with one of the worst clinical outcomes. Following the repurposing of auranofin as an antibacterial against Gram-positive bacteria, we previously synthetized auranofi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…All treatments substantially improved larval survival relative to no treatment controls, demonstrating the model’s usefulness in screening novel anti- Burkholderia agents (Thomas et al 2013 ). Finally, two auranofin analogues active against Burkholderia clinical isolates in vitro were of low toxicity in G. mellonella , warranting further investigation for their therapeutic potential (Maydaniuk et al 2021 ).…”
Section: Burkholderia Pseudomallei and Burkholderi...mentioning
confidence: 99%
“…All treatments substantially improved larval survival relative to no treatment controls, demonstrating the model’s usefulness in screening novel anti- Burkholderia agents (Thomas et al 2013 ). Finally, two auranofin analogues active against Burkholderia clinical isolates in vitro were of low toxicity in G. mellonella , warranting further investigation for their therapeutic potential (Maydaniuk et al 2021 ).…”
Section: Burkholderia Pseudomallei and Burkholderi...mentioning
confidence: 99%
“…The drug combinations with synergy scores above 15 calculated by all models were considered synergistic; between -5 and 15 were deemed to be additive, whereas synergy scores below -15 were considered antagonistic. Synergy scores represent the mean response deviated from the reference model due to interactions between the combined drugs [ 14 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…316 derivatives are active against Helicobacter pylori and bacteria from the Burkholderia genus. 317,318 Another study has also shown that auranofin inhibited, in a concentration-dependent manner, the growth of Helicobacter pylori TrxR (Gram-negative bacteria) and showed synergistic or additive effect with known H. pylori antibiotics such as amoxicillin or metronidazole and clarithromycin. Also, when the phosphane ligand on auranofin was replaced by Nheterocyclic carbene as shown in Figure 20, stability and inhibitory activity of the complexes were not altered greatly, and they show reduced in vitro toxicity.…”
Section: Antibacterial Gold Complexesmentioning
confidence: 99%
“…Their study also revealed that the thiol ligand is necessary for the bactericidal activity of both Gram-positive and Gram-negative bacteria . Other reports from this lab have also shown that auranofin and its derivatives are active against Helicobacter pylori and bacteria from the Burkholderia genus. , …”
Section: Therapeutic Gold Complexesmentioning
confidence: 99%